2018
DOI: 10.1002/hep.29586
|View full text |Cite
|
Sign up to set email alerts
|

Exosome miR‐335 as a novel therapeutic strategy in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common and deadly cancer. Most cases of HCC arise in a cirrhotic/fibrotic liver, indicating that environment may play a paramount role in cancer genesis. Previous studies from our group and others have shown that, in desmoplastic cancers, there is a rich intercellular communication between activated, cancer-associated fibroblasts and cancer cells. Moreover, extracellular vesicles (EVs), or exosomes, have been identified as an important arm of this intercellular communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 34 publications
(62 reference statements)
0
157
0
5
Order By: Relevance
“…The function of the substance in HCC exosomes Long noncoding ribonucleic acid expression and promoting sensitivity of cancer cells to chemotherapy[117].Fang Wang and other researchers have found that stellate cell-derived EVs could load miR-335-5p. What makes us exhilarated is that miR-335-5 could be introduced into HCC cells to inhibit tumor growth and metastasis, which thereby provides a new treatment strategy for liver cancer[118]. Another research by Kenji Takahashiet al have found that during the process of mediating chemotherapeutic stress response, RNAi-mediated knockdown of EVs (exosomes) lncRNAs could reduce the function and progression of tumor cells in HCC, which promotes the treatment of HCC[119].…”
mentioning
confidence: 99%
“…The function of the substance in HCC exosomes Long noncoding ribonucleic acid expression and promoting sensitivity of cancer cells to chemotherapy[117].Fang Wang and other researchers have found that stellate cell-derived EVs could load miR-335-5p. What makes us exhilarated is that miR-335-5 could be introduced into HCC cells to inhibit tumor growth and metastasis, which thereby provides a new treatment strategy for liver cancer[118]. Another research by Kenji Takahashiet al have found that during the process of mediating chemotherapeutic stress response, RNAi-mediated knockdown of EVs (exosomes) lncRNAs could reduce the function and progression of tumor cells in HCC, which promotes the treatment of HCC[119].…”
mentioning
confidence: 99%
“…Furthermore, exosomes isolated from human hepatic stellate (LX2) cells were loaded with miR-335-5p and these exosomes were taken up by HCC cells in vitro and in vivo. This preclinical study showed an inhibition of HCC cell proliferation and invasion in vitro and also demonstrated HCC tumour shrinkage in vivo upon uptake of these engineered exosomes [50] . There are several advantages of using exosome-based therapy, as exosomes show low immunogenicity, toxicity and are stable in tissue and in circulation.…”
Section: Exosomes As Delivery Vehicles For Hcc Therapeuticsmentioning
confidence: 64%
“…In addition, the overexpression of miR-320a in CAFs has been reported as an effective method to produce miR-320a-enriched exosomes that can transfer this miRNA to HCC cells, thus suppressing proliferation, migration, and metastasis when binding to its direct target, PBX3 [66]. The same approach was used to down-regulate the expression of several key genes that induce proliferation and invasion of HCC cells by taking advantage of HSC-derived exosomes loaded with tumor suppressor miR-335-5p [106]. Another study provided a novel approach to pack miR-26a into exosomes to selectively target HCC cells through the scavenger receptor, resulting in the inhibition of cell migration and proliferation [107].…”
Section: Targeting Tumor Microenvironment Cells Using Exosomal Mirnasmentioning
confidence: 99%